Peaceful Families for Migrant Workers: A Book Perspective Adabul Islam Fi Nidzomil Usroh - Muhammad Ihwan; Fahmi Basyar (Program Pascasarjana Universitas Ibrahimy, 2025)
Forming a Sakinah Family in a family building is not easy, sometimes a new problem arises when we want to solve another problem. In this case, a head of the family who is a migrant worker, of course there are many obstacles faced in sailing the family ship, because a Sakinah family can be realized if it has a strong foundation, namely the head of the family as a leader in the family. So the head of the family has an obligation to guide his children and wife to be better. Then the relationship between parents and children is also important so that the family can be said to be an Islamic family. Good communication with children can provide a warm and harmonious atmosphere in the family. If the points above are met, then building an Islamic family, a family that has peace will be easier to realize.